Spatiotemporal trajectories of reactivation of somatosensory cortex by direct and secondary pathways after dorsal column lesions in squirrel monkeys - Qi, Hui-Xin (Neuroimage, 2016)
After lesions of the somatosensory dorsal column (DC) pathway, the cortical hand representation can become unresponsive to tactile stimuli, but considerable responsiveness returns over weeks of post-lesion recovery. The reactivation suggests that preserved subthreshold sensory inputs become potentiated and axon sprouting occurs over time to mediate recovery. Here, we studied the recovery process in 3 squirrel monkeys, using high-resolution fMRI CBV-fMRI mapping of contralateral somatosensory cortex responsiveness to stimulation of distal finger pads with low and high level electrocutaneous stimulation (ES) before and 2, 4, and 6 weeks after a high cervical level contralateral DC lesion. Both low and high intensity ES of digits revealed the expected somatotopy of the area 3b hand representation in pre-lesion monkeys, while in areas 1 and 3a, high intensity stimulation was more effective in activating somatotopic patterns. Six weeks post-lesion, and irrespective of the severity of loss of direct DC inputs (98%, 79%, 40%), somatosensory cortical area 3b of all three animals showed near complete recovery in terms of somatotopy and responsiveness to low and high intensity ES. However there was significant variability in the patterns and amplitudes of reactivation of individual digit territories within and between animals, reflecting differences in the degree of permanent and/or transient silencing of primary DC and secondary inputs 2 weeks post-lesion, and their spatio-temporal trajectories of recovery between 2 and 6 weeks. Similar variations in the silencing and recovery of somatotopy and responsiveness to high intensity ES in areas 3a and 1 are consistent with inter-individual differences in collateral damage to and recovery of secondary (e.g. spinothalamic) pathways. Thus, cortical deactivation and subsequent reactivation depends not only on the degree of DC lesion, but also on the severity and duration of loss of secondary as well as primary inputs revealed by low and high intensity ES.